Review of scribal education in ancient Israel: The Old Hebrew epigraphic evidence by Christopher Rollston - Hewett, Matthew R (Lingua Frankly, 2018)
In this illustrative and thorough article, Christopher Rollston argues for the existence of, in R’s words, “a formal, standardized scribal education” in Ancient Israel (47). R bases his argument on a systematic analysis of the epigraphic evidence of Old Hebrew (i.e. Iron Age II Hebrew, ca. 1000-550 ce) and offers the following as his supporting arguments: (i) In terms of the ductus, the stance, and the relative spatial relationship of graphs, the Old Hebrew (OH) script: (a) displays synchronic consistency, (b) demonstrates discernable, diachronic development, and (c) differs markedly from those of nearby polities (Phoenicia, Arameans); (ii) In terms of orthography, the OH script exhibits synchronic (and arguably regional) consistency with distinctive features that were in opposition with the features of the Phoenician and Aramaic national scripts; and (iii) In terms of content, hieratic numerals (which derive from a complex number system originally borrowed from Egypt) were inscribed on many OH documents, suggesting that an administrative or governing body routinized their usage (and practical dissemination) throughout Iron Age Israel